Strategies to Increasing Locally-Generated Revenue from Hotel Taxes in Padang City - Rully Caesario; A. Faroby Falatehan; Sri Mulatsih (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2023)
One of Padang City's sources of local revenue is hotel taxes. This study aims to analyze the potential of hotel tax revenue and the factors that influence hotel tax revenue, as well as to formulate strategies to increasing hotel tax revenue in the city of Padang. The primary data collection used a purposive sampling technique, while the Slovin method was used to determine the 60 hotel samples to reveal the average hotel rates. The analytical method used is the analysis of potential tax calculations, multiple linear regression, the SWOT and the QSPM matrix. The results show the potential for hotel taxes that can be optimized in the amount of Rp 17,6 billion to Rp 35,9 billion. Factors that affect hotel tax revenues in Padang City are occupancy rates and the number of hotel rooms. One of the strategies that can be implemented to increasing hotel taxes is to socialize information about the importance of tax obligations to regionally registered and unregistered hotel taxpayers and service providers.